A beryllium-selective microcantilever sensor modified with benzo-9-crown-3 functionalized polymer brushes. Issue 22 (31st May 2017) - Peng, Rong-Peng; Xing, Ling-Bao; Wang, Xiao-Jun; Wu, Cheng-Juan; Chen, Bin; Ji, Hai-Feng; Wu, Li-Zhu; Tung, Chen-Ho
Abstract : Benzo-9-crown-3 functionalized polymer brushes were prepared via surface-initiated atom transfer radical polymerization on the gold surface of microcantilevers for the selective detection of Be 2+ . Abstract : Benzo-9-crown-3 functionalized polymer brushes were prepared via surface-initiated atom transfer radical polymerization on the gold surface of microcantilevers for the selective detection of Be 2+ . Other metal ions, such as Li +, Na +, K +, Mg 2+ and Ca 2+, have minimal effect on the deflection response of the microcantilevers. The microcantilever sensor exhibits high sensitivity for beryllium ions with a limit of detection (LOD) as low as 10 −10 M. The mechanism of bending is discussed as well.